Legal Analysis of the Determination of the Age Limit of Children Related to Sexual Crimes Committed by Children (ABH) in the Perspective of Law Enforcement in Indonesia and International Law - Sumartini, Raden Siti; Hamja, Hamja; Fathurrahman, Farhan (Gema Wiralodra, 2024)
The development of sexual crimes against children, both children as perpetrators or children as victims lately is very concerning. Sexual crimes are greatly influenced by time and place. The high level of human civilization and the phenomenon of globalization that increasingly knows no boundaries, in this case, is the negative impact of the influence of globalization also contributes to the emergence of various crimes of sexual harassment. Often crimes or criminality occur around our lives, including on the streets or public spaces. From the presentation, the formulation of the problem will arise, namely how is the Status and Position of Children in the positive legal system of Indonesia and International Law? What is the form of legal protection for children who have committed criminal acts in Indonesia's positive law? How is the concept of legal reform on the determination of children's age limits so that they can make a positive contribution to law enforcement?        The methodology used in the study uses a normative legal research method (doctrinal research) which mainly analyzes primary legal materials and secondary legal materials, in this case the researcher also complements the method of interviewing sources that is autorotac, because its nature is more focused on conceptualizing ideas in the form of models, so that the expected results can be applied by policy makers. Violations of the law that have been committed by a child, of course, in terms of law enforcement, are treated differently (diversion) from the procedures applied by adults. Therefore, researchers argue that there is a shift in understanding related to the age of children and people who are considered adults at this time, remembering the fact that some children are not yet 18 years old, but they are physically and psychologically mature. Based on the above explanation, according to the author, it is important to be able to conduct a study on the age limit of children so that they are limited legal subjects because this can be a measure for law enforcement and can provide legal protection for children who are facing the law.